EDUCATION ON THE MANAGEMENT OF HEALTH PROTOCOLS TO AVOID THE TRANSMISSION OF COVID-19 - Reny Sulistyowati; Fina Ratih Wira Putri Fitri Yani; Yuyun Christyanni; Agus Agus; Dedi Cahyo Nusantoro (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2021)
Introduction: Since the COVID-19 pandemic that occurred in Indonesia and face-to-face learning in schools has been replaced by online methods, this does not mean that school students can be free from the transmission of the COVID-19 virus. There are still no banners, and educational activities on the prevention of the COVID-19 virus for residents of the MAN City School Palangka Raya. The purpose of this community service activity is to increase knowledge and awareness for students in carrying out health protocols, one of which is also to prepare for face-to-face learning.Methods: Online Implementation of activities for 50 students of MAN City School Palangka Raya, the activity began by taking care of the administration of permits to schools, followed by the implementation of a series of activities in the form of education about COVID-19 and how to implement health protocols in the school environment following the guidelines of the Ministry of Health of the Republic of Indonesia.  The method of activity is done by teaching and Q&A. Before giving pre-test material and afterward post-test.Results: After being given education, the post-test score of knowledge about COVID-19 showed an increase in the average score of 13%.  Participants seemed enthusiastic at the discussion session, indicated by the number of questions from participants. Conclusion: Health protocol management education can increase participants' knowledge.